PRE-SERVICE EFL TEACHERS’ PERCEPTIONS TOWARD THE DEVELOPMENT OF HYBRID LEARNING MODEL MATERIALS - Samsul Khabib (Premise: Journal of English Education and Applied Linguistics, 2023)
Recent innovations in online education have created an opportunity for hybrid learning, combining online and traditional learning. Hybrid learning leads to particular challenges for pre-service teachers, such as the way to manage the materials. Furthermore, hybrid learning materials can be developed using technology to create multimedia content that is more interactive than traditional print materials. Digital tools such as video, sound, animations, and graphics are powerful tools in the teacher's hands to engage learners and provide immersive learning experiences. This study aims to investigate pre-service teachers' perceptions of hybrid learning materials development. The mixed-method approach with questionnaire, documentation, and interview was employed to gain the data. The study result has shown that pre-service teachers perceive technology in a positive light when it is used for teaching purposes appropriately. Given this information, policymakers suggested having an investment in developing hybrid-learning materials.